ATP9B, a P4-ATPase (a Putative Aminophospholipid Translocase), Localizes to the trans-Golgi Network in a CDC50 Protein-independent Manner - Takatsu, Hiroyuki (American Society for Biochemistry and Molecular Biology, 2011)
Type IV P-type ATPases (P4-ATPases) are putative phospholipid flippases that translocate phospholipids from the exoplasmic (lumenal) to the cytoplasmic leaflet of lipid bilayers and are believed to function in complex with CDC50 proteins. In Saccharomyces cerevisiae, five P4-ATPases are localized to specific cellular compartments and are required for vesicle-mediated protein transport from these compartments, suggesting a role for phospholipid translocation in vesicular transport. The human genome encodes 14 P4-ATPases and three CDC50 proteins. However, the subcellular localization of human P4-ATPases and their interactions with CDC50 proteins are poorly understood. Here, we show that class 5 (ATP10A, ATP10B, and ATP10D) and class 6 (ATP11A, ATP11B, and ATP11C) P4-ATPases require CDC50 proteins, primarily CDC50A, for their exit from the endoplasmic reticulum (ER) and final subcellular localization. In contrast, class 2 P4-ATPases (ATP9A and ATP9B) are able to exit the ER in the absence of exogenous CDC50 expression: ATP9B, but not ATP11B, was able to exit the ER despite depletion of CDC50 proteins by RNAi. Although ATP9A and ATP9B show a high overall sequence similarity, ATP9A localizes to endosomes and the trans-Golgi network (TGN), whereas ATP9B localizes exclusively to the TGN. A chimeric ATP9 protein in which the N-terminal cytoplasmic region of ATP9A was replaced with the corresponding region of ATP9B was localized exclusively to the Golgi. These results indicate that ATP9B is able to exit the ER and localize to the TGN independently of CDC50 proteins and that this protein contains a Golgi localization signal in its N-terminal cytoplasmic region.